2018
DOI: 10.1007/s00262-018-2214-0
|View full text |Cite
|
Sign up to set email alerts
|

High-grade glioma associated immunosuppression does not prevent immune responses induced by therapeutic vaccines in combination with Treg depletion

Abstract: High-grade gliomas (HGG) exert systemic immunosuppression, which is of particular importance as immunotherapeutic strategies such as therapeutic vaccines are increasingly used to treat HGGs. In a first cohort of 61 HGG patients we evaluated a panel of 30 hematological and 34 plasma biomarkers. Then, we investigated in a second cohort of 11 relapsed HGG patients receiving immunomodulation with metronomic cyclophosphamide upfront to a DC-based vaccine whether immune abnormalities persisted and whether they hampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…The tumour-controlled extracellular communication is critical to promote the progression switch mechanisms and diminish antitumor processes, including immune surveillance [ 3 , 4 ]. In response to the tumour-derived factors, both, resident and peripheral immune cells, including CD4 + regulatory T cells (Tregs), eosinophiles, monocytes and resident microglia, undergo reprogramming that results in altered secretory capacity and phagocytic functions [ 4 , 5 , 6 , 7 ]. The crosstalk between glioma cells and the heterogenic immune population is mediated by suppressive cytokines that disturb the balance of proliferation and apoptosis, and switch the activity phenotype from M1 to M2.…”
Section: Introductionmentioning
confidence: 99%
“…The tumour-controlled extracellular communication is critical to promote the progression switch mechanisms and diminish antitumor processes, including immune surveillance [ 3 , 4 ]. In response to the tumour-derived factors, both, resident and peripheral immune cells, including CD4 + regulatory T cells (Tregs), eosinophiles, monocytes and resident microglia, undergo reprogramming that results in altered secretory capacity and phagocytic functions [ 4 , 5 , 6 , 7 ]. The crosstalk between glioma cells and the heterogenic immune population is mediated by suppressive cytokines that disturb the balance of proliferation and apoptosis, and switch the activity phenotype from M1 to M2.…”
Section: Introductionmentioning
confidence: 99%
“…Accuracies of AUC = 0.9-1.0 (13) and a sensitivity 95% and specificity of 85% (19), have been found. However, IL-1b (21,24) and IL-6 (21,22,25,26) concentrations were also found to not be changed compared to controls or even decreased in glioma patients compared to FIGURE 2 | Overview of possible blood-based biomarkers for glioma and their purposes. Schematic overview of the several biosources (plasma, serum, extracellular vesicles, blood platelets, circulating immune cells, and circulating glioma tumor cells) and biomolecules (proteins, nucleic acids, metabolomics and peptides) that are identified for patients with glioma.…”
Section: Interleukinsmentioning
confidence: 99%
“…In glioma patients it was often observed that WBC counts were increased compared to controls (21,54,55,100,118,220). However, it was also found that leukocytes are not significantly changed in glioma patients compared to controls (21,194), potentially due to dexamethasone use (221)(222)(223)(224).…”
Section: White Blood Cellsmentioning
confidence: 99%
“…Altogether, these data led to removal of PGE 2 from DC maturation cocktails by several groups [11]. In our own brain tumor vaccination program, we have used TNFα and IL-1ß as maturing agents so far and validated this combination as the standard for generation of clinical-grade DCs under GMP [12,13].…”
Section: Introductionmentioning
confidence: 99%